The Effect of Giving a Combination of Tomato Juice and Virgin Coconut Oil on Total Cholesterol and LDL Levels - Sutrisno; Mayta Sari Dwianggimawati; Velinda Fitria Rahayu; Duwi Rahmawati (Universitas STRADA Indonesia, 2025)
Cholesterol and Low Density Lipoprotein (LDL) can be harmful to the body if they are present in large amounts in the blood, causing deposits on the walls of blood vessels and narrowing. The purpose of this study was to determine the effect of giving tomato juice and virgin coconut oil on changes in total cholesterol and LDL levels. This research design was a pre-experiment with the One Group Pretest-Posttest approach, conducted at the Blabak Village Posbindu. The population in this study were all hypercholesterolemia sufferers at the Blabak Village Posbindu as many as 60 people, with a random sampling technique and a sample of 20 respondents. The measuring instrument used was a lipid profile examination, tested with a Paired sample T-Test. The results of the study showed that the average change in total cholesterol levels was 26.10 mg/dl and most respondents experienced a significant decrease in LDL of around 20-30mg/dl.